Aortic root dissection with left valsalva sinus perforation detected by transesophageal 3D echocardiography in a patient with Behçet's disease. Issue 1 (12th January 2013) - Zhao, Hang; He, Ben; Shen, Xuedong; Qiao, Zhiqing; Xu, Tingyan; Lian, Feng; Xue, Song
<x xml:space="preserve">Abstract</x> Behçet's disease (BD) is a multi‐system inflammatory disorder. We report the case of a BD patient with severe aortic root vasculitis. Two‐dimensional transthoracic echocardiography (2DE) images suggested left Valsalva sinus aneurysm ruptured into the left ventricular outflow tract. However, preoperative transesophageal real‐time 3‐dimensional echocardiography (3DE) revealed that the aneurysm‐like structure involved most of the left ventricular outflow tract wall, leading to the diagnosis of aortic root dissection associated with perforation of the left Valsalva sinus and prolapse of the exfoliated endocardium into the left ventricular outflow tract. These findings were confirmed by open heart surgery. 3DE was helpful differentiating aortic root dissection from Valsalva sinus aneurysm rupture, especially by demonstrating the extent of aneurysm‐like structure in the left ventricular outflow tract. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound42:59–62, 2014